2019
DOI: 10.13052/jwe1540-9589.18462
|View full text |Cite
|
Sign up to set email alerts
|

A Semantic Web Approach to Enable a Smart Route to Historical Archives

Abstract: In this paper we show that an ontology-based approach can be beneficial for enhancing the access to cultural resources, and in particular historical documents. The paper starts with an overview of our approach, aimed at providing online archival systems with a semantic layer based on Semantic Web standards (OWL 2 and RDF). Two projects are introduced, namely Harlock900 and PRiSMHA, carried out in collaboration with local cultural institutions owning rich historical archives. In particular, the paper describes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…That is to say the coordinate of a super node vector is a linear combination of the other super node vector of a network in Cartesian coordinate system. Thus, relative positions and skeleton of a network are preserved by the distances between each pair of super nodes [7,9].…”
Section: Shortest Path Between Super Nodesmentioning
confidence: 99%
“…That is to say the coordinate of a super node vector is a linear combination of the other super node vector of a network in Cartesian coordinate system. Thus, relative positions and skeleton of a network are preserved by the distances between each pair of super nodes [7,9].…”
Section: Shortest Path Between Super Nodesmentioning
confidence: 99%
“…PRiSMHA starts from the assumption that only a layer of semantically rich metadata can support an actual enhancement of the access to archival resources, an approach supported by several researchers in the area of Digital Humanities; see, for instance, (Motta et al, 2000). Exactly as a good human archivist, a smart digital one needs to "know" the content of the available documents in order to be able to retrieve all and only the relevant ones, independently of the words actually used to report them in the primary sources; a case study supporting this claim can be found in (Goy et al, 2019b). This implies that the system needs a detailed semantic knowledge of the domain, i.e.…”
Section: Introductionmentioning
confidence: 99%